Development and Justification of a Self-Regulating System for Adjusting the Angle of Rotary Tiller Blade with a Vertical Rotation Axis - Tarverdyan, A. P.; Altunyan, A. V.; Grigoryan, A. S. (ՀԱԱՀ հիմնադրամ)
The article considers the problem of providing constant or almost constant values of the blade cutting angles during one rotation of the tiller rotor with a vertical rotation axis. Analytical expressions were obtained by analyzing the trajectory of the tiller knife/blade, which enable to determine the change of the blade cutting angles at a constant location and to define the patterns of this change in the ranges of (0...π) and (π...2π). The derived expressions and conclusions make it possible to adjust the location angle of the knife, using a pattern, in case of which the cutting angles of the knife will remain unchanged during one rotation of the rotor. This circumstance is important from the prospect of ensuring a uniform working mode of the rotary tiller.
Keywords: Agricultural Engineering